Zambia's Farmer Input Support Program and Recommendations for Re-designing the Program - World Bank (World Bank, Washington, DC, 2021)
This note provides recommendations for redesigning Zambia’s Farmer Input Support Program (FISP) in the context of international experience with other similar programs, especially those in Africa. The objective of this note is to provide recommendations that can help in improving the current programs providing subsidized inputs to farmers, through enhancing the efficiency of the program, targeting the right beneficiaries, value perceived by beneficiary farmers, and probably bringing in savings. The note is a key deliverable under the Advisory Services work carried out by the Bank on strategies for food security in Zambia and Zimbabwe. This note has three sections following the summary: (i) a brief review of the evidence generated on input subsidy programs; (ii) specific recommendations for Zambia’s Farmers Input Support Program, and (iii) recommendations on complementary investments.